IMPROVING CONSTRUCTION LOGISTICS PERFORMANCE THROUGH COMMUNICATION - EL HAMAD, RAMI; YASIN, AHMED (My University, 2021)
Even though construction logistics is an important phase of the construction industry, it is one of the most challenging one. Communication and collaboration are seen as two of the most vital elements in achieving a successful construction logistics plan. The construction logistics is an emerging topic being studied and discussed. However, there is less studies about the communication part of the construction logistics. Therefore, this study has been conducted to identify the connection between communication and logistics and its biggest problems that the construction industry is currently suffering from. Furthermore, it is also investigated how digital systems can contribute to a simplified construction logistics and improved construction logistics communication. The study was conducted through an abductive method that linked literature and the interview study. The study shows that communication problems in construction logistics are primarily the result of inadequate planning. It is vital that construction logistics communication is included in the planning process. The fact that the building industry is reluctant to adopt new methods and solutions does not make it any easier for further development.
Keywords: Construction; logistics; communication; strategies; technological solutions; third-party-logistics; just-in-time and collaboration